Euthanasia - Wroński, Konrad; Bocian, Roman; Cywiński, Jarosław; Dziki, Adam (Contemporary Oncology/Współczesna Onkologia, 2008)
Since the 1970s there has been a discussion concerning whether euthanasia should be made legal and ethical in the case of patients with a terminal disease. The word euthanasia is of Greek origin and means putting an incurably sick person to a good death in order to shorten their suffering. At the present time euthanasia is legal in Belgium, Luxemburg, the Netherlands and in the state of Oregon in the USA. In Poland euthanasia is illegal and is regarded as a crime. The following article presents several aspects related to euthanasia in Poland.